Pneumatosis intestinalis as a manifestation of chronic intestinal volvulus: case report - Peña-González, Ricardo-Raziel; Arellano-López, Ricardo-Paul; Hernández, Erick Fernando; Contreras-Díaz, Brandon-Rafael; Ramírez-Miguel, Williams O.; Aguilera-Callejas, Eduardo; Quiroz-Alvarez, Jonathan; Gutiérrez-Uvalle, Gabriela E. (International Surgery Journal, 2024)
The pneumatosis cystoides intestinalis (PCI) is a rare disease characterized by presence of gaseous cysts containing nitrogen, hydrogen and carbon dioxide in the intestinal wall that can be idiopathic or associated with other diseases. There are 5 theories about the pathophysiology: mechanic (obstruction), immunosuppression (atrophy of Peyer's patches), bacterial (Clostridium spp.), pulmonary (chronic pulmonary disease) and chemical (exposure to trichloroethylene). The aim of this paper is to present a clinical case of a patient with rheumatic comorbidity admitted to the emergency service and diagnosed with acute abdomen secondary to intestinal volvulus associated with pneumatosis intestinalis.